2016
DOI: 10.1021/acs.est.6b04819
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Haloacetonitriles, Haloacetamides, and Nitrogenous Heterocyclic Byproducts by Chloramination of Phenolic Compounds

Abstract: 18The potential formation of nitrogenous disinfection by-products (N-DBPs) was investigated from the 19 chloramination of nitrogenous and non-nitrogenous aromatic compounds. All molecules led to the 20 formation of known N-DBPs (e.g., dichloroacetonitrile, dichloroacetamide) with various production 21 yields. Resorcinol, a major precursor of chloroform, also formed di-/tri-chloroacetonitrile, di-/tri-22 chloroacetamide, and haloacetic acids, indicating that it is a precursor of both N-DBPs and 23carbonaceous D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 45 publications
3
40
0
Order By: Relevance
“…Interestingly, the aromatic nature of hydroxybenzamide did not favour HAcAm formation as much as expected during both chlorination and chloramination. Literature suggests that a ring-cleavage reaction is triggered when the aromatic ring is activated by the hydroxyl group, encouraging chlorine electrophilic substitution (Chu et al, 2010b;Hureiki et al, 1994;Nihemaiti et al, 2016). However, either chloramine cannot trigger the rapid opening of the benzene ring (Chu et al, 2009) or the HAcAms previously formed at lowercontact times, regardless of their amount, were prone to hydrolyse at a faster rate.…”
Section: Formation Of Nitrogenous Disinfection By-products (Hacams and Hans)mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the aromatic nature of hydroxybenzamide did not favour HAcAm formation as much as expected during both chlorination and chloramination. Literature suggests that a ring-cleavage reaction is triggered when the aromatic ring is activated by the hydroxyl group, encouraging chlorine electrophilic substitution (Chu et al, 2010b;Hureiki et al, 1994;Nihemaiti et al, 2016). However, either chloramine cannot trigger the rapid opening of the benzene ring (Chu et al, 2009) or the HAcAms previously formed at lowercontact times, regardless of their amount, were prone to hydrolyse at a faster rate.…”
Section: Formation Of Nitrogenous Disinfection By-products (Hacams and Hans)mentioning
confidence: 99%
“…However, recently Huang et al (2012) found that DCAcAm can be generated independently from DCAN during both chlorination and chloramination. That study suggested the need for investigating alternative pathways and potential nitrogenous and non-nitrogenous N-DBP precursors in drinking water during the application of chlor(am)ine (Chu et al, 2010a(Chu et al, , 2010bKimura et al, 2013;Le Roux et al, 2016;Nihemaiti et al, 2016). Interestingly, the DCAcAm yields reported from model precursor studies, that include amino acids, are significantly lower than those of DCAN (Chu et al, 2010b), whereas in studies that include real water matrices the levels of the two N-DBP groups are similar (mean: 1.4 µg/L and 1 µg/L, respectively) (Krasner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In past decades, Mn-oxides have been used to remove antibacterials and compounds with phenolic and fluoroquinolonic moieties [20,21], triazine, aromatic N-oxides [22], tetracyclines [23], and estrogenic compounds such as the synthetic hormone 17R-ethinylestradiol [24,25] and as an alternative treatment for wastewater or groundwater containing DIC because Mn-oxides are cheap and operated-friendly [26,27]. These compounds may be endocrine disruptors (EDS) and precursors of harmful disinfection byproducts such as haloacetonitriles, haloacetamides, and nitrogenous heterocyclic [28].…”
Section: Introductionmentioning
confidence: 99%
“…However, the simultaneous presence of chloramines and chlorine reacting with DOM can increase overall DBP production (Wang et al, 2016), and the reaction of monochloramine with DOM and other trace chemical contaminants can produce N -nitrosodimethylamine and other species such as aromatic halogenated DBPs (Pan and Zhang, 2013; Hua et al, 2015; LeRoux et al, 2016; Pan et al, 2016; LeRoux et al, 2017; Jiang et al, 2017; Tian et al, 2017) that can be more toxic than trihalomethanes and haloacetic acids, but are currently not as widely regulated (Krasner et al, 2013; Pan et al, 2013; Gong et al, 2016; Guo et al, 2016; Nihemaiti et al, 2016; Zeng et al, 2016; Spahr et al, 2017). The specific timing of chloramination in the water treatment train is thus very important; chloramines need to be generated at specific times that allows for maximum microbial inhibition while minimizing harmful DBP formation (Carlson and Hardy, 1998; Hua and Reckhow, 2007; Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%